M141 Impact Of Beta-blockade On Exercise Capacity And Dynamic Hyperinflation In People With And Without Copd Awaiting Vascular Surgery. (10th November 2014) - Key, A; Parry, M; West, M; Jack, S; Torella, F; Duffy, N; Walker, PP
Abstract : Beta-blockers have a key role in the management of heart failure but have been under-utilised in people with COPD due to fear of bronchoconstriction and its impact on symptoms and function. Beta-blockers are also used peri-operatively in people undergoing vascular surgery due to improved cardiac function though this practice is contentious due to a risk of post-operative complications, particularly stroke. As part of a study looking at the impact of beta-blockade in people under abdominal aortic aneurysm surveillance we examined the impact of beta-blockade on CPET variables and dynamic hyperinflation at peak exercise 55 subjects were recruited though only 46 completed incremental CPET off and on beta-blockers. Mean age was 70 (6) years and 42 (91%) were male. IHD or heart failure was diagnosed in 13 people and COPD diagnosed in 7. However, 24/46 (52%) had post-bronchodilator airflow obstruction consistent with COPD (10 mild, 10 moderate and 4 severe). 18 were routinely prescribed beta-blockers (mainly bisoprolol). Those taking beta-blockers stopped treatment for the second CPET and other subjects commenced weight-adjusted bisoprolol before the second CPET. The 25 COPD subjects had a mean FEV1 of 2.14 (0.62) L, FEV1 predicted 76 (20)% and FEV1 /FVC 0.54 (0.11). The main results are shown in the table . Compared with the subjects without COPD at peak exercise the COPD subjects had slightly lower VO2, work and ventilatory equivalents but these did not differ significantly. When beta-blocked both COPD and non-COPD subjects had a lower heart rate (p < 0.001) and consequently oxygen pulse (p < 0.001) but there was a minimal effect on other variables. The COPD patients showed a greater fall in IC (p = 0.02) but the addition of a beta-blocker did not have any additional effect. The 7 subjects already diagnosed with COPD did not differ from the whole COPD group. In an unselected clinic population with arterial vascular disease a majority of people had, mostly undiagnosed, COPD albeit predominantly mild to moderate. Continuation or commencement of beta-blockers had little effect on level of peak exercise or degree of dynamic hyperinflation. This supports the use of beta-blockers in this COPD population, both in a peri-operative setting and for a cardiac indication.